2009
DOI: 10.2527/jas.2009-1983
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: A gene delivery system in the embryonic cells of avian species using a human adenoviral vector

Abstract: Adenovirus (Ad) has been used in vivo and in vitro as a vector to carry a foreign gene for efficient gene delivery into various cell types and tissues of animals. The aim of the current study was to evaluate the Ad delivery system in primary avian cells. Primary cells isolated from the embryonic pectoralis major muscles of the chicken and quail were cultured and incubated with human recombinant Ad serotype 5 (Ad5) containing sequences encoding either the green fluorescence protein (GFP) gene alone, as a tracki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…More recently, genome-edited ducklings were successfully produced by an adenoviral infection into blastoderms, indicating the efficacy of genome editing technology with adenoviruses in poultry and water birds other than chickens and quails [ 47 ]. Previous studies also confirmed the transduction potential of adenovirus type 5 in chicken, quail, and turkey cells [ 48 , 49 ]. However, this method may not be suitable as a knock-in system because the CRISPR/Cas9 system and donor template must both be delivered into the same cells, indicating low efficiency.…”
Section: Current Approaches For Avian Genome Editing Based On the Cri...supporting
confidence: 67%
“…More recently, genome-edited ducklings were successfully produced by an adenoviral infection into blastoderms, indicating the efficacy of genome editing technology with adenoviruses in poultry and water birds other than chickens and quails [ 47 ]. Previous studies also confirmed the transduction potential of adenovirus type 5 in chicken, quail, and turkey cells [ 48 , 49 ]. However, this method may not be suitable as a knock-in system because the CRISPR/Cas9 system and donor template must both be delivered into the same cells, indicating low efficiency.…”
Section: Current Approaches For Avian Genome Editing Based On the Cri...supporting
confidence: 67%
“…To explore whether the approaches used in the present study for genome editing can be used in other poultry species, the efficiency of adenovirus-mediated gene expression was examined. In our previous cell culture study, a highly desirable transduction efficiency and gene expression of the adenovirus type 5 in quail and chicken embryonic cells were confirmed (16). In addition, we investigated the transduction efficiency of the adenovirus in turkey embryonic cells (SI Appendix, Fig.…”
Section: Analysis Of Adenoviral Vector Integration and Off-target Mutmentioning
confidence: 89%
“…Direct injection of the adenoviral CRISPR/Cas9 vector into the blastoderm provides a rapid way to generate knockout birds by avoiding the need for PGC culture and genome modification in vitro before injection into the embryo. In addition, this method can be broadly applied to other poultry species because of the high transduction efficiency of the adenovirus into other avian cells, including the chicken (16) and turkey (SI Appendix, Fig. S3).…”
Section: C T G G a T T G C C G C T T C T Wt C C T G G A T T G C C Gmentioning
confidence: 99%
“…Importantly, this method can potentially be applied to various avian species, as long as cells are receptive to adenoviral transduction, because adenovirus can be injected into any avian blastoderms. So far, transduction feasibility of adenovirus type 5 in chickens, quail, and turkey cells has been confirmed [71,75,76], and in vivo genome editing in quail, using the adenovirus-mediated method, has been reported [71,72]. However, limitations of the adenovirus-mediated method should also be considered.…”
Section: Adenovirus-mediated Methodsmentioning
confidence: 99%
“…In contrast, the adenovirus-mediated method was recently introduced and is only applied in quail, so far. Nevertheless, this method can be potentially applied to generate various GE avian species for scientific and industrial purposes if adenovirus can deliver target genes to cells of various avian species, in addition to chickens, turkeys, and quail [71,75,76]. For example, GE zebra finch can be a good model to investigate the human language-learning process because of a comparable vocal and language-learning process between songbirds and human [137].…”
Section: Future Research and Conclusionmentioning
confidence: 99%